1966
DOI: 10.1039/tf9666202191
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase chlorine-photosensitized oxidation of trichloroethylene

Abstract: The chlorine-photosensitized oxidation of trichloroethylene in the gas phase has been investigated at 363 and 403°K. Dichloroacetyl chloride is the main reaction product and its rate of formation is given by d[CnHCl@]/dt = L[O2l/(k + k'[021).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
24
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 0 publications
8
24
0
Order By: Relevance
“…The product formed, C(O)Cl 2 , is a major product of the TCE oxidation, as shown by experimental studies. [9][10][11][12] Our results concur with the previous literature suggesting addition of the OH to the less substituted carbon. [17][18][19] This is reflected in the lower activation energy barrier, 1.7 kcal · mol -1 for reaction 3, whereas OH addition to carbon 2 (reaction 2) has a barrier of 4.2 kcal · mol -1 .…”
Section: Resultssupporting
confidence: 96%
“…The product formed, C(O)Cl 2 , is a major product of the TCE oxidation, as shown by experimental studies. [9][10][11][12] Our results concur with the previous literature suggesting addition of the OH to the less substituted carbon. [17][18][19] This is reflected in the lower activation energy barrier, 1.7 kcal · mol -1 for reaction 3, whereas OH addition to carbon 2 (reaction 2) has a barrier of 4.2 kcal · mol -1 .…”
Section: Resultssupporting
confidence: 96%
“…which is similar to that reported for the reaction of C,C15(8) [2], C,HCI,(8) [7] and C,H5(8.8) [l] with 0,. The rate of the inhibited photochlorination being independent of the total pressure (no influence of added N2), the rate of reaction step(p) (see eq.…”
Section: Equation (Xiii) Holds For Reaction (3) Of Schema (Vi) Comsupporting
confidence: 88%
“…Huybrechts and Meyers [10] and Bertrand et al [11] previously studied the Cl-initiated oxidation of trichloroethylene at , and found that the T Ն 357 K principal oxidation product was CHCl 2 C(O)Cl (Ն 88%), while detecting CCl 2 O in lower yields. They did not observe CHClO, which presumably decomposed at these higher temperatures and/or is much more reactive towards Cl atoms, which were in higher concentrations than in the present work.…”
Section: Relative Rate Study Of the Reactionmentioning
confidence: 98%